Impact of Thermal Effluent from a Coal Power Station on the Variability of Benthic Diatoms Composition - Nurfarahaisha, Binti Roslan (Universiti Malaysia Sarawak (UNIMAS), 2014)
Sejingkat Coal Power Station discharges a large volume of warm effluent into the river. This could give some impact on the aquatic organisms. The objectives of the study are i) to identify diatoms taxa in the study area for month of December 2013 until March 2014 ; ii) to estimate relative abundance of each benthic diatom taxa found in the study area ; iii) to record selective water quality parameters (temperature, dissolved oxygen, pH, salinity) and chlorophyll a concentration from December 2013 to March 2014 ; iv) to assess the relationship between physico-chemical parameters with chlorophyll a in all the sampling stations. The methods used were categorized into sampling strategy and laboratory analysis, cleaning of diatom frustules, and preparation of diatoms permanent slide. The result of this study revealed that the trend that five most common diatoms occurring in the sediment were Actinocyclus sp., Cyclotella sp., Manguinea sp., Synedra sp., and Coscinodiscus sp., while Navicula sp. and Synedra sp. were consistently inhibiting on rocks at the study area. The water parameters (temperature, dissolved oxygen, pH, and salinity) were significantly different along the sampling points. Even though there were significant changes happen to the physico-chemical parameters of water, the benthic diatoms communities were still inhibiting the area.